2015
DOI: 10.1093/carcin/bgv005
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 and AP-1 cooperatively upregulate integrin α5 expression to induce invasion and the epithelial–mesenchymal transition

Abstract: Epithelial-mesenchymal transition (EMT) is an important process implicated in tumor invasion and metastasis. Twist1 is a transcription factor that induces EMT, including E-cadherin suppression and cancer cell migration and invasion; hence it promotes cancer metastasis. Twist1 directly or indirectly regulates the expression of various genes and cellular functions involved in cancer progression. However, the underlying mechanisms remain largely unknown. In this study, we investigated the molecular basis for Twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…On the other hand, we previously reported that ZEB2 directly interacts/cooperates with Sp1 to function as a transcriptional activator of mesenchymal genes (vimentin, integrin α5, and cadherin-11) to induce invasion [53]. We also found that functional cooperation between Twist1 and AP-1 induces EMT and invasion [54]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we previously reported that ZEB2 directly interacts/cooperates with Sp1 to function as a transcriptional activator of mesenchymal genes (vimentin, integrin α5, and cadherin-11) to induce invasion [53]. We also found that functional cooperation between Twist1 and AP-1 induces EMT and invasion [54]. …”
Section: Discussionmentioning
confidence: 99%
“…The EMT is characterized by morphological changes from epithelial to spindle-shaped mesenchymal like cells, increased cell size, loss of cell adhesion as consequence of changes in integrin expression, in particular α 5 β 1 overexpression [15], increased invasiveness and expression of mesenchymal markers especially vimentin [32, 33]. CPS has been found to induce EMT in colon cancer cells [16], but no data on BC has been provided so far.…”
Section: Discussionmentioning
confidence: 99%
“…EMT, characterized by morphological and molecular changes of cancer cells with increase of mesenchymal-related proteins, plays a pivotal role in the acquisition of malignant features such as invasion, metastasis and chemoresistance [14, 15]. In this regard, CPS induces EMT in colon cancer cells by modulating the reactive oxygen species (ROS) production and the AKT/mTOR pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…41 For invasion assays, cells (50,000 per well) were plated in serum-free medium on 24-well trans-well inserts (Costar) coated with 100 ml/well of Matrigel (BD Biosciences, #354234, 250 mg/ml) and 100 ml/well of collagen I (the underside; Sigma, C7661, 20 mg/ml). When mitomycin C (Sigma, M4287, 1 mg/ ml) was added, FBS-containing medium was used instead of serum-free medium.…”
Section: Trans-well Assaysmentioning
confidence: 99%